FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN KONSERVATISME AKUNTANSI PADA PERUSAHAAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA, BURSA MALAYSIA DAN SINGAPORE STOCK EXCHANGE TAHUN 2010-2014 - Mamesah, Melisa; Saerang, David P.E.; Lambey, Linda (ACCOUNTABILITY, 2016)
Conservatism is the precautionary principle in uncertainty. There are many cases of accounting frauds occurred due to lack of conservatism implementation resulting financial statements are overstated. This study aims to analyze the affect of firm size, leverage, institutional ownership and audit committee to the implementation of conservatism in the insurance companies listed on Bursa Efek Indonesia, Bursa Malaysia and Singapore Stock Exchange. In this study, conservatism measured by market to book ratio. Used as sample of 11 companies. The analytical method used in this research is multiple regression. The results of this study are firm size and audit committee positively affect the implementation of conservatism. On the other hand, leverage and institutional ownership negatively affect the implementation of conservatism. Keywords: conservatism, firm size, leverage, institutional ownership, audit committee